Discrimination of the Gypsy Population in the University Environment - Jesús María Aparicio-Gervás; Miguel Ángel Carbonero-Martín; Lorena Valdivieso-León; Raquel Vázquez-Ramil (Education Sciences)
The Roma population is one of the most discriminated social groups. Ignorance of their culture, traditions, etc. generates prejudices and stereotypes that hinder the processes of intercultural coexistence. The aim is to make the Roma people visible and to intervene in the university population, promoting intercultural and inclusive learning spaces to reduce behaviors that generate inequalities. Students from the University of Valladolid were involved, 1255 students in particular, distributed in control and experimental groups. The instrument consists of 40 closed questions and one open-ended. A quantitative analysis was carried out in the anti-Gypsy attitudes categories with t-tests. Item to item differences were not significant in categories A, B and C, but there were differences in D between the experimental and the control groups, which confirms important trends in the target population. Prejudices towards the Roma population continue to exist. University students who receive training have fewer prejudices than students who do not, although other variables can influence the process. Of the students, 72.2% are disturbed by the same negative behaviors, regardless of the ethnic group, and half of them are disturbed by behaviors based on prejudices. It is confirmed the need for preventive interventions to avoid the establishment of erroneous beliefs about the Roma community.